DENIM FABRIC PROPERTIES AND ANALYSIS (Journal of Science-Innovative Research in Uzbekistan, 2025)
Denim is one of the most common materials in the world's fashion industry, distinguished by its durability, unique texture and practical properties. This article will analyze in detail the history, physical and chemical properties, production technologies and environmental impact of denim fabric. The article will highlight the importance of denim in modern industry and reveal its development prospects.